“The sisters did her every imaginable injury”: Power and violence in «Cinderella» - Alcantud Díaz, María (International Journal of English Studies, 2012)
The main aim of this article is to discuss the results achieved after investigating the presence of violence in the Grimm brothers’ Cinderella with the intention of finding out what kind of processes predominate in this tale and whether they can be related to violent actions. The analysis involved firstly, a study of the frequency and concordances of some words belonging to the semantic field ‘violence’, surveying in detail the context in which they appear and secondly, the analysis of transitivity processes. The method proved to be a good strategy to check whether each character’s identity and social position (power) were somehow related to the infliction of violence within this context. As a general conclusion drawn from the analysis of the results, a tentative proposal could be formulated: a corpus-based analysis in conjunction with both, a transitivity analysis and a Critical Discourse Analysis could empirically detect the presence of controversial topics such as violence in different types of texts.